2007
DOI: 10.1016/j.biochi.2006.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-dependent surface transport of the proton pumping ATPase: A model to study plasma membrane biogenesis in yeast

Abstract: The proton pumping H þ -ATPase, Pma1, is one of the most abundant integral membrane proteins of the yeast plasma membrane. Pma1 activity controls the intracellular pH and maintains the electrochemical gradient across the plasma membrane, two essential cellular functions. The maintenance of the proton gradient, on the other hand, also requires a specialized lipid composition of this membrane. The plasma membrane of eukaryotic cells is typically rich in sphingolipids and sterols. These two lipids condense to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
(63 reference statements)
2
30
0
Order By: Relevance
“…Changes in the membrane permeability of C. dubliniensis in response to farnesol treatment have also been reported (20). Lipid rafts are associated with specific proteins, such as Pma1p in S. cerevisiae (49) and GPI-anchored proteins in S. cerevisiae (1) and mammalian cells (5). Interestingly, we have shown that several genes involved in GPI anchor biosynthesis have decreased expression in C. parapsilosis following exposure to farnesol, correlating with the changes in the localization of the lipid raft.…”
Section: Discussionmentioning
confidence: 84%
“…Changes in the membrane permeability of C. dubliniensis in response to farnesol treatment have also been reported (20). Lipid rafts are associated with specific proteins, such as Pma1p in S. cerevisiae (49) and GPI-anchored proteins in S. cerevisiae (1) and mammalian cells (5). Interestingly, we have shown that several genes involved in GPI anchor biosynthesis have decreased expression in C. parapsilosis following exposure to farnesol, correlating with the changes in the localization of the lipid raft.…”
Section: Discussionmentioning
confidence: 84%
“…1C). Because many membrane proteins require a proper lipid environment to achieve their proper conformation (39,40), it seems probable that disrupted lipid balance can increase protein misfolding.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the protonpumping H 1 -ATPase, Pma1, reveal some of these functions (90). Pma1 has been a valuable model for determining how proteins are transported from the ER to the plasma membrane, and readers are directed to published reviews for more detailed information (91,92). Like all integral membrane proteins, Pma1 becomes part of the hydrophobic membrane in the ER, where lipids must contribute to the microenvironment necessary for the correct folding of Pma1 into a functional conformation.…”
Section: Secretory Pathway Endocytosis and The Plasma Membranementioning
confidence: 99%